Reconstruction of the Aortic Arch in Newborns and Infants Using an Extended End-to-End Anastomosis - Truba, Iaroslav P.; Dziuryi, Ivan V.; Sekelyk, Roman I.; Golovenko, Oleksandr S. (Ukrainian Journal of Cardiovascular Surgery, 2021)
The problem of the effectiveness of obstruction at the level of the aortic arch is still a matter of discus-sion in the modern literature. Traditionally, by excision of the coarctation part, in the presence of hypoplasia, the incision is extended to a narrowed area and a modification of the classical end-to-end anastomosis is applied in the form of an elongated or expanded variant. Recently, when proximal part is involved in the pathological process, cardiac surgeons have been more likely to use median sternotomy using other types of plastic surgery, including dilation of the narrowed area with a pericardial patch, or pulmonary artery tissue. Accordingly, the analysis of the results of the use of end-to-end anastomosis in young children with aortic arch hypoplasia, especially in view of long-term survival and the level of reoperation, is an important issue of neonatal cardiac surgery. The aim. To evaluate the effectiveness of the use of an extended end-to-end anastomosis after reconstruction of the aortic arch in children under 1 year of age. Materials and methods. The study material included 348 infants who underwent surgical correction of aortic arch hypoplasia through the method of extended end-to-end anastomosis from 2010 to 2020. The operations were performed at the National Amosov Institute of Cardiovascular Surgery of the NAMS of Ukraine and the Ukrainian Children’s Cardiac Center. The study group included only patients with two-ventricular physiology. There were 233 male patients (67%) and 115 female patients (33%). The mean age was 1.07 (0.20; 2.30) months, the mean weight was 3.89 (3.30; 4.90) kg, the mean body surface area was 0.23 (0.20; 0.28) m2. Diagnosis of aortic arch hypoplasia was based on two-dimensional echocardiography. Results. According to echocardiography, after surgery there was a significant decrease in the pressure gradient in the aortic arch from 48.3 ± 20.3 to 16 ± 6.9 (p<0.05), left ventricular PV increased significantly from 61.6 ± 12% to 66.3 ± 6.4% (p> 0.05). The hospital mortality was 1.7% (n = 6). The causes of mortality were not related to the end-to-end aortic arch technique. The duration of follow-up period ranged from 1 month to 9.3 years. Two deaths occurred in the follow-up period. Thirty-two (9.1%) patients developed aortic arch restenosis in the postoperative period. Balloon dilatation of restenosis was performed in 21 patients. Eleven patients underwent repeated aortic arch repair surgery through the median sternotomy. There were no central nervous system complications in the follow-up period. Conclusions. The use of an extended end-to-end anastomosis in the surgical treatment of aortic arch hypoplasia demon strates low hospital mortality and high long-term survival. Indications for the effective use of this type of reconstruction are hypoplasia of the isthmus and distal aortic arch.